The question and the method in the exposition of Aristotle's four causes (2011)
We have two different expositions of the four cause’s theory in Aristotle. We find one in Metaphysics A and the other in Physics II, 3. Although they are equal regarding their content, they differ in respect to the form of the exposition. When we ask for the reason of this difference, we can see that although the theory is the same in both places, it is animated by different questions in each place, because it is inside different sciences.  The question that is guiding the exposition in Physics looks for the principles of movement, while the one guiding the investigation in the book A of Metaphysics looks for the first universal  principles of being qua being, that is the entity, weather sensible or incorruptible. The exposition in Metaphysics A is a dialectical and genealogical one, because the interest is to show the grasp of the final cause and the necessity of it, from where it derives the foundation of theology as a science distinct from physics and as the primary one.